Cytotoxic and Osteoblast Differentiation Induction Properties of Crude Polar Extract of Piper sarmentosum leaves: Cytotoxicity and differentiation effect of P. sarmentosum - Intan Zarina Zainol Abidin; Anis Nabilah Johari; Zaidah Zainal Ariffin; Muhammad Dain Yazid; Herryawan Ryadi Eziwar Dyari; Shahrul Hisham Zainal Ariffin (Journal of Tropical Life Science, 2023)
Piper sarmentosum or ‘kaduk’ is a well-known herb plant in Malaysia. Its extracts were found to exhibit a bone-protective effect against osteoporotic rats. Our study aim is to morphologically observe the effect of P. sarmentosum ethyl acetate extract on the differentiation of human peripheral blood stem cells (PBSCs) into osteoblasts. P. sarmentosum extracts (1-900 µg/mL) prepared using 1% dimethyl sulfoxide (DMSO) were used in the cytotoxicity assay. Then, the differentiation assay was performed using concentrations of 1-50 µg/mL. The untreated cells acted as the negative control, while the cells cultured in 50 µg/mL ascorbic acid and 10 mM β-glycerophosphate was a positive control. The cytotoxicity effect and proliferation capacity of the cells were analyzed using Trypan Blue exclusion method, while the differentiation of PBSCs was observed using von Kossa staining and ALP gene expression analysis. The result showed a decrease in cells’ viability in a dose-dependent manner during cytotoxicity assay. After 14 days of the differentiation, a constant rate of proliferation could be observed in the treated cells and positive control, while the untreated cells showed an increase in proliferation. The mineralization of extract-treated cells showed significant differences (p<0.05) as compared to the negative control. The expression of ALP was also upregulated on day 14 of differentiation compared to day 0. In conclusion, the extract was capable to induce osteoblast differentiation of human peripheral blood stem cell and potential to be used in tissue regeneration